Pendekatan Budaya dan Kesejahteraan Sosial di Taman Nasional Komodo untuk Mendukung Keamanan Nasional - Jeihany Anggrilla Safarani; Agus Adriyanto; Herlina Juni Risma Saragih (Journal of Education on Social Science (JESS), 2022)
Komodo National Park is a medium in maintaining national identity to support the implementation of national defense and maintain national security. Komodo National Park is one of five national parks that were first designated in Indonesia with the main icon being the endemic animal, the Komodo. Then, the Government runs this park management model using a participatory approach to tourism development accompanied by the provision of training to develop human resources, capital assistance, to equipment assistance which is synergized and integrated with environmental care institutions and conservation organizations. This research uses a qualitative approach with a literature study by searching and studying various literatures related to culture and welfare in Komodo National Park so that the data in this study uses secondary data. The legacy of the Ora legend that provides behavioral construction to the local community until the next generation builds a sense of belonging among the people to maintain the unity of Indonesia and live peacefully side by side with Komodo according to the provisions of the zoning area. This is the basis for how the government carries out development efforts with community participation which is accommodated in activities that accommodate creativity, interest, and potential such as creative economic training to improve the level of community welfare. The conclusion in the research: national security which is manifested in the management of Komodo National Park describes the societal security and environmental security sectors.